2021
DOI: 10.1002/ppul.25704
|View full text |Cite
|
Sign up to set email alerts
|

The ISPAT project: Implementation of a standardized training program for caregivers of children with tracheostomy

Abstract: Background: Tracheostomy-related morbidity and mortality mainly occur due to decannulation, misplacement, or obstruction of the tube. A standardized training can improve the skills and confidence of the caregivers in tracheostomy care (TC).Objective: Our primary aim was to evaluate the efficiency of standardized training program on the knowledge and skills (changing-suctioning the tracheostomy tube) of the participants regarding TC.Materials and Methods: Sixty-five caregivers of children with tracheostomy were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Several studies have provided simulation or mannequin‐based training on standardized TC and scenarios that may be challenging for caregivers and have found training to significantly increase caregiver knowledge 14–19 . Woodbridge et al designed a simulation‐based training program for 20 caregivers of neonatal and pediatric patients with new tracheostomy and found that caregivers’ competence and comfort with skill and scenario increased after training 17 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have provided simulation or mannequin‐based training on standardized TC and scenarios that may be challenging for caregivers and have found training to significantly increase caregiver knowledge 14–19 . Woodbridge et al designed a simulation‐based training program for 20 caregivers of neonatal and pediatric patients with new tracheostomy and found that caregivers’ competence and comfort with skill and scenario increased after training 17 .…”
Section: Discussionmentioning
confidence: 99%
“…13 In the second step, standardized theoretical and practical training of caregivers was performed by the train ed healthcare providers, and the caregiver knowledge and skill scores immediately post-training were evaluated. 14 In the third step, we investigated the overall outcomes of the training and examined the level of knowledge and skill retained 1 year later (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations